2003
DOI: 10.1103/physrevc.67.017001
|View full text |Cite
|
Sign up to set email alerts
|

Λ-Λ interaction andΛΛ6He

Abstract: A one-boson exchange ͑OBE͒ potential model, based on the Nijmegen model D potential, for the 1 S 0 , SϭϪ2 interaction is analyzed with emphasis on the role of coupling between the ⌳⌳, N⌶, and ⌺⌺ channels. Singlet scalar exchange, an approximation to two-pion exchange, is significant in all channels; surprisingly, the one-pion exchange component is almost negligible. The size of the channel coupling as a function of the overall strength of the OBE model potential is examined. Implications of the analysis for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 14 publications
6
54
0
Order By: Relevance
“…We note that, contrary to what it seems to be implied in Ref. [30], the coupling between the ⌳⌳ and ⌶N channels is important even when the interaction is weak, as it is the case of the NSC97e potential used here which produces a scattering length of about −0.5 fm. Actually, in Refs.…”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…We note that, contrary to what it seems to be implied in Ref. [30], the coupling between the ⌳⌳ and ⌶N channels is important even when the interaction is weak, as it is the case of the NSC97e potential used here which produces a scattering length of about −0.5 fm. Actually, in Refs.…”
Section: Resultsmentioning
confidence: 40%
“…In fact, the important role of the coupling to ⌺⌺ states has been recently pointed out in Ref. [30] and explicitly worked out for the Nijmegen interactions in the variational calculation of Ref. [31].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is an important problem how to take account of other states beyond the 1s shell. It was shown that the ΛΛ − ΞN coupling contributes to the 6 ΛΛ He binding energy sizably (though not so much for realistic interactions) [16,17,18], despite that all the nucleonic 1s states are occupied. In our approach, highly-excited components are renormalized into the effective ΛΛ interactions in some approximate way, as commented in the end of Subsec.…”
Section: A Modelmentioning
confidence: 99%
“…Theoretically, the ΛΛ − ΞN coupling in ΛΛ hypernuclei 1 have been considered by several groups [6,12,14,15,16,17,18,19]. Mostly, hypernuclei observed experimentally have been studied, namely, 6 ΛΛ He [12,16,17,18],…”
Section: Introductionmentioning
confidence: 99%
“…This technique minimizes off-shell effects since at very low momentum the neutron is practically a spectator in the deuteron. Another method (Afnan et al, , 2003Bissey et al, 2001;Petratos et al, 2006) is to perform deep inelastic scattering from 3 He and 3 H at very high x.…”
Section: G the Neutron Structure Functionmentioning
confidence: 99%